Media Massa: Pencipta Industri Budaya Pencerahan yang Menipu Massa Studi Simulacra dan Hiperrealitas Film AVATAR - Yoyoh Hereyah (ULTIMA Comm, 2011)
Globalization affects virtually all aspects of the society, including cultural aspects. Culture can be defined as values embraced by society or perception held by citizens of various things. Globalization as a symptom of the range of the values and culture of particular overlooks the world (so that it becomes ‘world culture') have been seen since long. The Film is a form of mass media that bring values, cultures and ideologi of his creator. The concept of cultivations of cultural values is embedded through the ideas, stories, characters, special effects and the distribution of a film. Avatar upholds the value and ideologi from its producers. Keywords: film studies, globalization, hegemony, hyperreality, simulacra